Теоретико-методичні основи комплексного анализу та оцінювання екологічності природно-техногенних об’ектів - Kozulia, T. V.; Emelianova, D. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2016)
The new approach in assessing the natural and anthropogenic objects’ state from the sustainable development point of view based on the different stages of their study is proposed. The comprehensive assessment based on MIPS-analysis and risk-estimation of the state of economic, ecological, and social constituent objects are used to improve the quality of decision-making to reduce the risk level in the natural and anthropogenic complexes’ state. This article offers the algorithmic support for implementing the comprehensive methodology for assessing the conformance of ecological, social, and economical aspects of systems to ecological quality requirements.